Regulatory T Cell Metabolism in Atherosclerosis - Baardman, Jeroen; Lutgens, Esther (Metabolites, 2020)
Regulatory T cells (Tregs) are capable of suppressing excessive immune responses to prevent autoimmunity and chronic inflammation. Decreased numbers of Tregs and impaired suppressive function are associated with the progression of atherosclerosis, a chronic inflammatory disease of the arterial wall and the leading cause of cardiovascular disease. Therefore, therapeutic strategies to improve Treg number or function could be beneficial to preventing atherosclerotic disease development. A growing body of evidence shows that intracellular metabolism of Tregs is a key regulator of their proliferation, suppressive function, and stability. Here we evaluate the role of Tregs in atherosclerosis, their metabolic regulation, and the links between their metabolism and atherosclerosis.